2016
DOI: 10.1177/1687814016674628
|View full text |Cite
|
Sign up to set email alerts
|

Surface integrity and fatigue analysis of shot-peening for 7055 aluminum alloy under different high-speed milling conditions

Abstract: To study the effect of different milled surfaces on shot peening surface integrity (roughness, residual stress, hardness, and microstructure), research on the change of surface integrity is carried out using the same shot peening process for different milling surfaces of 7055-T77 aluminum alloy. Surface integrity measurements, fatigue fracture analysis, and fatigue life tests are conducted to reveal the effect of surface integrity on crack initiation and fatigue life. The results show that shot peening can red… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 21 publications
0
6
0
Order By: Relevance
“…SP140 specimen has the lowest COF as compared with other specimens. The enhancement in the surface integrity and microstructure by SP contributed to yield low COF value [31]. Besides, Figure 4(c) is more discernible that the treated composites are having the lowest wear rate which is attributed essentially to the NC structure and dislocation density improved by virtue of SP.…”
Section: Wear Behaviormentioning
confidence: 91%
“…SP140 specimen has the lowest COF as compared with other specimens. The enhancement in the surface integrity and microstructure by SP contributed to yield low COF value [31]. Besides, Figure 4(c) is more discernible that the treated composites are having the lowest wear rate which is attributed essentially to the NC structure and dislocation density improved by virtue of SP.…”
Section: Wear Behaviormentioning
confidence: 91%
“…This may be due to the fact that shot peening homogenised the features [38] of the machined/built surfaces (as shown in Fig. 6) and also applies enhanced local stress conditions [39]. The only exception was with WEDM, as shown in Fig.…”
Section: The Influence Of Machining Process and Shot-peening On Fatigue Performancementioning
confidence: 99%
“…The underlying mechanism for the residual stress variation is due to the combined effects of the mechanical and thermal deformations. 13 When the cutting time is further increased, the increased cutting temperature induces the thermal deformation which tends to produce the tensile residual stress. Therefore, the longer continuous cutting time can seriously change the pattern of the residual stress distribution and it is advised to shorten the working time by adjusting the cutting parameters in order to obtain the required compressive stress.…”
Section: Evolution Of Residual Stress Distributionmentioning
confidence: 99%
“…Wu et al 12 investigated the milling deformation of aluminum alloy using the quasi-symmetric machining method. Yao et al 13 concluded that the maximum residual compressive stress and the depth of residual stress layer increased significantly after shot peening, and the residual stress and hardening distribution are very good. In addition, Shaw 14 and Astakhov 15 found that the chip shape shows an important relationship with the mechanical and thermophysical properties of the workpiece material.…”
Section: Introductionmentioning
confidence: 99%